Burning the breeze : three generations of women in the American West - Hendrickson, Lisa (University of Nebraska Press, 2021)
"Burning the Breeze is the family story of three generations of women who, having begun their journey by fleeing Missouri during the Civil War, flouted gender expectations to create and successfully run guest ranches in Montana and Arizona"--